Dochody i wydatki publiczne w Polsce w porównaniu ze Stanami Zjednoczonymi i krajami Unii Europejskiej - Kowalik, Paweł (Public Revenues And Expenditures In Poland In The Comparison With The United States And The European Union Countries, 2008)
Poland underwent the period of the political transformation and became is a member of the European Union. For the public finance and regulations connected with them they are unusually important events. They changed the essential layout of social relations occurring in the process of collecting and spending public funds. A purpose of this article is comparing the general level of profits and expenses in Poland, the USA and the EU.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 342-349